Teaching of Mathematics and Science in English: The Teachers' Voices - Yahaya, Mohamad Fadhili; Mohd Noor, Mohd Asri; Mokhtar, Ahmad Azman; Mohd Rawian, Rafizah; Othman, Mahmod; Jusoff, Kamaruzaman (2009)
The policy to change the medium of instruction in the teaching of Mathematics and Science from Bahasa Melayu (Malay Language) to English in 2003 is an important innovation affecting not only the students but also teachers of Mathematics and Science. However, how far do the changes affect the teachers is the issue addressed in the paper. In fact the objectives of the study were to investigate the reaction of the mathematic and science teachers to using English as the medium of instruction, the problems encountered by these teachers in using English in the classroom and the availability of language support systems. A study was conducted on a group of pre-university educators in the northern part of Malaysia who have undergone language enhancement courses known as English for the Teaching of Mathematics and Science (ETeMS). The study reveals that teachers of mathematics and science are generally perceptive of the change in the medium of instruction but needing some sustainable measures to not only improve their language ability and delivery. Thus it is hope that certain measures would be taken to address on teachers struggle to ensure the success of the policy.